Determination of MHD mode structures using soft x-ray diagnostics in TCV. (1st March 2023) - Dreval, M B; Sharapov, S E; Vallar, M; Labit, B; Karpushov, A N; Garcia-Munoz, M; ,
Abstract: A forward modeling technique is developed for determining the characteristic features of observed MHD modes from the line-of-sight data of the soft x-ray (SXR) diagnostics with 64 vertical lines-of-sight in theTokamak à Configuration Variable tokamak. Using diagnostics with excellent spatial resolution, this technique is shown to evaluate the poloidal mode numbers m, radial location and ballooning character of the MHD modes. In the first stage, the poloidal mode structures are modeled by the radially localized Gaussian-shaped emission regions rotating along the magnetic flux surfaces. In the second stage, the space structures of observed 95–100 kHz toroidal Alfvén eigenmodes (TAEs) are investigated numerically using HELENA, CSCAS and MISHKA codes. The calculated TAE eigenfunctions are then used in our forward modeling similarly to the approach of contrast imaging diagnostics (Edlund et al 2009 Phys. Rev. Lett. 102 165003) and SXR diagnostics (Piovesan et al 2008 Nucl. Fusion 48 065001). A ballooning structure of the observed n = 1 TAE mode can be analyzed more easily due to the low poloidal mode number m in contrast to the high- m modes analyzed by a similar SXR technique in the W7-X stellarator (Dreval et al 2021 Plasma Phys. Control. Fusion 63 065006).